2017
DOI: 10.1098/rsos.160959
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive seasonality, sex ratio and philopatry in Argentina's common vampire bats

Abstract: Common vampire bats (Desmodus rotundus) are a key rabies vector in South America. Improved management of this species requires long-term, region-specific information. To investigate patterns of demography and dispersal, we analysed 13 642 captures of common vampire bats in Northern Argentina from the period 1969–2004. In contrast with findings from more tropical regions, we found reproductive seasonality with peak pregnancy in September and peak lactation in February. Curiously, sex ratios were consistently ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 59 publications
5
66
0
2
Order By: Relevance
“…Consequently, we suggest that the importance of juveniles reflects many pathogens responding similarly to the influx of susceptible individuals, either through heightened transmission following a birth pulse or increased viral shedding by nursing females (Plowright et al, 2008). An effect of susceptible juveniles on viral communities is consistent with observed seasonal variation in individual vampire bat viruses due to birth pulses (Delpietro et al, 2017), and could have implications for viral spillover if shedding of many pathogens simultaneously results in more opportunities for exposure. There are also implications for the use of culling to control vampire bats and their pathogens, as culling is thought to results in a juvenile-biased age structure (Streicker et al, 2012) and could therefore inadvertently increase viral community richness.…”
Section: Viral Richnesssupporting
confidence: 65%
See 1 more Smart Citation
“…Consequently, we suggest that the importance of juveniles reflects many pathogens responding similarly to the influx of susceptible individuals, either through heightened transmission following a birth pulse or increased viral shedding by nursing females (Plowright et al, 2008). An effect of susceptible juveniles on viral communities is consistent with observed seasonal variation in individual vampire bat viruses due to birth pulses (Delpietro et al, 2017), and could have implications for viral spillover if shedding of many pathogens simultaneously results in more opportunities for exposure. There are also implications for the use of culling to control vampire bats and their pathogens, as culling is thought to results in a juvenile-biased age structure (Streicker et al, 2012) and could therefore inadvertently increase viral community richness.…”
Section: Viral Richnesssupporting
confidence: 65%
“…This habitat generalism means that vampire bats live in colonies with extensive variation in climate, anthropogenic food resources and presence of other bat species. Colonies also vary in demographic traits that might impact viral community structure, such as population size, age structure and sex ratio (Delpietro, Marchevsky, & Simonetti, 1992;Delpietro, Russo, Carter, Lord, & Delpietro, 2017;Greenhall, Joermann, Schmidt, & Seidel, 1983;Streicker et al, 2012) (Table 1). As with most broadly distributed species, populations vary in their relative geographical proximity and genetic relatedness (Martins et al, 2009;, providing an opportunity to test the null expectation that viral community similarity declines with increasing geographical and genetic distance between populations (Nekola & White, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of Argentine vampire bats found that only about 15% of individuals were recaptured at the roost where they were initially captured (Delpietro, Russo, Carter, Lord, & Delpietro, 2017), while another study found no movement among Peruvian vampire bats in roosts located just 2.2 km apart (Streicker et al, 2012). Though we found no difference in beta diversity between sites, we did note increased heterogeneity of KK gut microbiotas compared with LAR, despite the fact that the bats at KK have more homogenous diets (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Co‐roosting of different bat species (Wohlgenant, ; Wray et al, ) could explain the phylogenetic relatedness between some genotypes detected in vampire bats and non‐haematophagous bats. However, even though D. rotundus share shelters with other bat species, they usually roost separately (Delpietro, Russo, Carter, Lord, & Delpietro, ). The bio‐geographical pattern of Bartonella species/genotypes resembles the pattern found for trypanosomes infecting D. rotundus .…”
Section: Discussionmentioning
confidence: 99%